Conceptions and Conceptual Changes of Junior High-School Students in the Topic of Temperature and Heat - Suharto Linuwih; Danastri Putri; Puji Asih (Program Studi Pendidikan Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2022)
The qualitative research was conducted in junior high school to know students’ conceptions and conceptual changes on temperature and heat, specifically on specific heat topics. This study uses the purposive sampling technique. The research was started by collecting data and observing the students. The next step was a try-out test instrument conducted in a regular eighth-grade class. The try-out test was used as an instrument test to the superior dan the regular class of seventh-grade and the superior class of eighth-grade. The research instrument was a conceptual test in essay form and then conducted an interview. The samples were the students who had many possibilities in answering the research instrument. Based on the result of the study, the students’ concepts can be divided into three types: scientific, alternative, and parallel. The conceptions of the excellent class of the seventh-grade, the regular class of seventh-grade, and the excellent class of eighth-grade are alternative concepts. The conceptual changes in the excellent eighth-grade class are decreasing students’ understanding of heat and temperature.